Association of microtubule-based processes gene expression with immune microenvironment and its predictive value for drug response in oestrogen receptor-positive breast cancer - Huang, Zhenfeng; Zhang, Minghui; Zhang, Nana; Zeng, Mengyao; Qian, Yao; Zhu, Meng; Meng, Xiangyan; Shan, Ming; Zhang, Guoqiang; Liu, Feng (Frontiers in Immunology, 2025)
ObjectiveThe development of acquired endocrine resistance and reduced chemosensitivity in oestrogen receptor-positive (ER+) breast cancer presents significant challenges. Microtubule-based process-related genes (MBPRGs) play essential biological roles in the cell cycle and the development of migration. This study aimed to establish a novel prognostic signature based on MBPRGs to improve patient outcomes and offer additional treatment options for those with ER+ breast cancer.MethodsClinical data along with relevant RNA information with ER+ breast cancer were sourced from The Cancer Genome Atlas and the Molecular Taxonomy of Breast Cancer International Consortium. Consensus clustering was subsequently utilised to identify new molecular subgroups. Evaluations of the tumour immune microenvironment and immune status of these subgroups were performed via ESTIMATE, CIBERSORT, MCP, and ssGSEA. Additionally, functional analyses were conducted to investigate the underlying mechanisms involved. Prognostic risk models were developed via random forest, support vector machines and the least absolute shrinkage and selection operator algorithm. Single-cell analysis revealed differences in the expression levels of key genes among various cell types. Western blotting was used to measure protein levels in breast cancer cell lines. Immunohistochemical staining was used to assess protein expression in paraffin-embedded tissues, and Kaplan–Meier survival curves were generated to evaluate survival differences between the high- and low-expression groups of key genes. Transwell and cell viability assays were used to examine the biological functions of CHORDC1.ResultsTwo molecular subgroups with significantly different survival outcomes were identified. Longer survival was linked to a high immune score, low tumour purity, a greater presence of immune infiltrating cells, and an overall positive immune status. Risk models derived from MBPRGs exhibited strong potential for predicting survival in patients with ER+ breast cancer. Key genes had elevated protein levels in differentiated breast cancer cell lines, and elevated CHORDC1 expression was linked to a tendency towards a worse outcome in patients with ER+ breast cancer. Silencing CHORDC1 inhibited cell viability and invasion, reducing sensitivity to tamoxifen and paclitaxel in vitro.ConclusionMBPRG expression is linked to the immune microenvironment and drug resistance in ER+ breast cancer patients, providing a reliable prognostic indicator for this group.